Performance evaluation and benchmarking : traditional -- Big data -- Interest of Things : 8th TPC Technology Conference, TPCTC 2016, New Delhi, India, September 5-9, 2016, Revised selected papers /: traditional -- Big data -- Interest of Things : 8th TPC Technology Conference, TPCTC 2016, New Delhi, India, September 5-9, 2016, Revised selected papers. (2017) - Unknown
No abstract available